Les campagnes urbaines: quels scénarios pour demain? - Pierre Donadieu (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
In this article, we will first analyze the political and socio-economic processes, which led to the disappearance of urban agriculture over the last 50 years. Then, we will illustrate how in the 21st century the concept of common urban landscape opens to new public policies related to the persistence of agricultural spaces and activities in urban areas. Last, we will describe three scenarios of agriculture and gardening, which can be developed in the same urban territory.